Hubungan Sosiodemografi dengan Hasil Klinis Pasien Covid-19 di RSUD Bengkulu - Lukas, Stefanus; Ramatillah, Diana Laila; Aldi, Yufri; Wahyuni, Fatma Sri; Gloria, Fransisca; Michael, Michael; Wahyudi, Agung Aji; Astari, Lita Tri (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Coronavirus disease 2019 (Covid-19) is an infectious disease caused by SARS-CoV-2 which has a shape and behavior resembling the SARS virus. The national mortality percentage is 4.23, which is above the national average. The purpose of the study was to determine what factors were associated with the deaths of Covid-19 patients at the Bengkulu Government Hospital. With the aim of knowing the sociodemographic relationship with the clinical outcomes of Covid-19 patients in Bengkulu. Methods A retrospective cohort study was conducted in this study. This study only involved patients with confirmed Covid-19, with a total sample of 127 patients who were hospitalized during April, May, and June 2021. + oseltamivir + vitamins as treatment. The outcome of Covid-19 infection had several significant correlation factors: age (0.0001), occupation (0.0001) and comorbidities (0.0001). In conclusion, the worst clinical outcomes were mostly found in patients with diabetes and those who were over 50 years old.